A per-stream coded bit loading algorithm for MIMO BIC-OFDM systems - Cheolkyu Shin; Hyuncheol Park; Joonhyuk Kang; Eunhye Nam (2010 International ITG Workshop on Smart Antennas, 2010)
This paper deals with bit-loading techniques for a multiple-input multiple-output bit-interleaved coded orthogonal frequency division multiplexing (MIMO BIC-OFDM) system. The per-stream coded bit loading algorithm is proposed based on a spatial domain power adaptation. For each spatial stream, a different power constraint is assigned using an initial power allocation (IPA) combined with the residual power diversion (RPD). Simulation results verify that the proposed bit loading scheme yields significant capacity gain compared to the existing bit loading algorithms. We also discuss a channel decomposition technique to reduce the feedback overhead.